THE EFFECT OF SHARIA FINANCIAL LEARNING AND SHARIA FINANCIAL LITERACY ON INVESTMENT INTENTION - Susilowati, Tetty; Santoso, Aprih (Journal of Islam and Science, 2018)
This study aims to: [1] analyze the effect of sharia financial learning on investment intention in Semarang University. [2] Analyzed the effect of sharia financial literacy on investment intention in Semarang University. This study uses quantitative analysis with multiple regression tests where there are three stages of analysis that must be carried out, namely: a partial significance test, a model feasibility test, and an analysis of the coefficient of determination. The population is active students who are taking Financial Management courses in Department of Management, Faculty of Economics, Semarang University in the academic year 2016/2017, as many as 97. Sampling in this study uses the Census method. The results of the study are: [1] sharia financial learning has a positive and significant effect on investment intention in students of Semarang University. [2] Sharia financial literacy has a positive and significant effect on investment intention in students of Semarang University.